Molecular basis of mast cell disease. Issue 1 (January 2015) - Soucie, Erinn; Brenet, Fabienne; Dubreuil, Patrice
Highlights Recurrent somatic mutations have been identified in mastocytosis patients. Distinct KIT mutants are associated with specific classes of mast cell disease. Epigenetic and splicing factor mutations are associated with aggressive mastocytosis. Epigenetic and splicing mutations occur early in disease ontology. SRSF2, TET2 and KITD816V mutations frequently occur together in patients.